2008
DOI: 10.1128/aac.01530-07
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resistance to Bacterial Infection in Protegrin-1 Transgenic Mice

Abstract: Antibiotic-resistant bacteria have become a public health concern. It was suggested that one source of resistant pathogens may be food-producing animals. Alternative approaches are therefore needed to enhance the resistance of farm animals to bacterial infection. Protegrin-1 (PG-1) is a neutrophil-derived antimicrobial peptide that possesses activity against a wide range of bacteria and enveloped viruses. Here we report on the production of transgenic mice that ectopically expressed PG-1 and compare their susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
5
18
1
Order By: Relevance
“…The TG pigs showed significantly lower bacterial burden in the lungs compared to that of the WT pigs. This finding is similar to those of previous reports, which demonstrated that the expression of an additional antimicrobial peptide can enhance the killing rate of bacteria in mice (4,5). Study 2 was designed to investigate whether the results obtained in study 1 showing reduced bacterial burden in the TG-challenged lungs minimized susceptibility to infection via contact exposure to infected pigs, which was more similar to the natural infection of this disease.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The TG pigs showed significantly lower bacterial burden in the lungs compared to that of the WT pigs. This finding is similar to those of previous reports, which demonstrated that the expression of an additional antimicrobial peptide can enhance the killing rate of bacteria in mice (4,5). Study 2 was designed to investigate whether the results obtained in study 1 showing reduced bacterial burden in the TG-challenged lungs minimized susceptibility to infection via contact exposure to infected pigs, which was more similar to the natural infection of this disease.…”
Section: Discussionsupporting
confidence: 73%
“…Expression of an additional porcine cathelicidin peptide, PR-39, in mice showed increased resistance to group A Streptococcus infection (4). Furthermore, enhanced resistance to Actinobacillus suis infection was observed in proptegrin-1 TG mice (5). These studies demonstrate that AMPs potentially can lead to the development of infection-resistant animals, at least in TG mouse models.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In comparison with their WT littermates, they exhibited enhanced resistance to APP bacterial infection as evidenced by their higher survival rate, lower tissue bacterial load, and milder histological severity after APP inoculation. These results were similar to those reported in the transgenic mice that exhibited ubiquitous expression of PG-1 under the control of a CMV promoter [20]. Yet, with the transgenic mice generated in the present study the likelihood of inducing bacterial resistance to antibiotics is further reduced as PG-1 expression is restricted to the respiratory tract only upon induction by bacterial infection.…”
Section: Discussionsupporting
confidence: 90%
“…In an attempt to develop new strategies for reducing antibiotic consumption in farm animal production, PG-1 was introduced as a transgene into the genome of mice which resulted in a significantly enhanced ability of these mice to fight against bacterial infections [20]. However, as the PG-1 transgene in these transgenic mice was driven by a constitutive promoter, resulting in the constant and ubiquitous expression of PG-1, development of microbial resistance would be very likely.…”
Section: Introductionmentioning
confidence: 99%